2014
DOI: 10.4236/acs.2014.43040
|View full text |Cite
|
Sign up to set email alerts
|

Minimum and Maximum Temperature Trends in Congo-Brazzaville: 1932-2010

Abstract: Maximum and minimum temperatures time series of Congo-Brazzaville are analyzed for trend and discontinuities over the period 1932 to 2010. Temperatures series show an irregular increase. A total of 8 synoptic stations show positive trends in their annual mean maximum temperature series, and 7 of them are significant, with higher trends for urban stations. Annual mean minimum temperature showed 6 stations having positive trends. This increase is in relation with observations at regional scale. However, the diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Furthermore, 20% of catchments showed negative trends while 80% of catchments showed positive trends in their diurnal temperature range. Samba & Nganga 16 analyzed maximum and minimum temperatures time series of Congo-Brazzaville, where the temperatures series showed an irregular increase. Moreover, 5 reported that in future the whole Zambezi River Basin is expected to become hotter, drier and more variable, experiencing more prolonged drought periods and more extreme floods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, 20% of catchments showed negative trends while 80% of catchments showed positive trends in their diurnal temperature range. Samba & Nganga 16 analyzed maximum and minimum temperatures time series of Congo-Brazzaville, where the temperatures series showed an irregular increase. Moreover, 5 reported that in future the whole Zambezi River Basin is expected to become hotter, drier and more variable, experiencing more prolonged drought periods and more extreme floods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The climate is tropical with a rainy season from October to May, and dry seasons between January-February and June-September. The annual rainfall oscillates among 1250 mm and 1350 mm/year [22]. The hydrogeological group is part of the Bateke's water table, with an area of 270 km 2 .…”
Section: Study Areamentioning
confidence: 99%
“…The study area has a tropical climate with a rainy season from October to May, and dry seasons between January-February and June-September. The annual fluctuation of rainfall is among 1250 mm and 1350 mm/year [18]. The hydrogeology is part of the Bateke's water table, with an area of 270 km 2 .…”
Section: Study Areamentioning
confidence: 99%